Exploring Factors Influencing College Students’ Motivation in Learning English: A Systematic Literature Review - Ananda Julianto, Dhika; Laeli, Nisvi; Nurkhafifah, Saskiya (Jurnal Bahasa Inggris, 2024)
Motivation significantly influences the success of English language learning among college students, making it a crucial area of study in educational research. Learning motivation is considered important due to its relationship with learning achievement; the higher the motivation, the better the learning outcomes students are likely to achieve. Despite this, its influence is rarely discussed because of a lack of awareness among participants in the learning process, specifically college students, lecturers, and institutional programs or regulations. This paper explores the factors influencing college students’ motivation in learning English. The study employs a systematic literature review covering the period from 2012 to 2024, analyzing ten relevant articles sourced from Google Scholar and the Directory of Open Access Journals (DOAJ). The findings highlight three primary categories of motivation: intrinsic motivation, driven by personal interest and enjoyment in learning English; extrinsic motivation, driven by rewards such as grades and peer influence; and combined motivation, driven by the integration of personal interest with external goals to sustain effort. The synthesis reveals the relationships among these motivational categories and highlights their harmony in developing suitable learning activities and optimizing educational programs in English language education. This study contributes insights into optimizing educational strategies to effectively utilize motivational factors and advises lecturers to maintain a positive attitude in the classroom to sustain students’ long-term motivation and improve learning outcomes.